2013
DOI: 10.1016/j.gaitpost.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Foot type biomechanics part 1: Structure and function of the asymptomatic foot

Abstract: Background Differences in foot structure are thought to be associated with differences in foot function during movement. Many foot pathologies are of a biomechanical nature and often associated with foot type. Fundamental to the understanding of foot pathomechanics is the question: do different foot types have distinctly different structure and function? Aim To determine if objective measures of foot structure and function differ between planus, rectus and cavus foot types in asymptomatic individuals. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
159
4
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(193 citation statements)
references
References 13 publications
16
159
4
14
Order By: Relevance
“…Similar findings have also been reported in studies that compared planus with normal foot posture, in which planus feet maintained a less everted position throughout gait [21,24]. As cavus feet display only slightly higher peak plantar pressure in the lateral heel compared to planus feet [25], it is possible that the rearfoot positioning found in our study is indicative of a strategy to centralise plantar pressure and reduce force applied to lateral structures of the foot. In contrast, Powell and colleagues [23] reported that planus feet exhibit greater peak eversion compared to cavus feet.…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings have also been reported in studies that compared planus with normal foot posture, in which planus feet maintained a less everted position throughout gait [21,24]. As cavus feet display only slightly higher peak plantar pressure in the lateral heel compared to planus feet [25], it is possible that the rearfoot positioning found in our study is indicative of a strategy to centralise plantar pressure and reduce force applied to lateral structures of the foot. In contrast, Powell and colleagues [23] reported that planus feet exhibit greater peak eversion compared to cavus feet.…”
Section: Discussionsupporting
confidence: 89%
“…Whereas foot type is related to foot function [2,13], it is important to perceive the difference of foot arch between ages and genders, to help prevent risk of injuries [14].…”
Section: Discussionmentioning
confidence: 99%
“…A százalékos különbségeknél az elhízottak adatait hasonlítottuk a normálértékekhez (n = 180) mtsai [36] a láb megváltozott struktúrája nélkül -pes planus, pes cavus -megnövekedett talpnyomásértékeket írtak le elhízottaknál a metatarsusok régiójában. Úgy tű-nik, hogy elhízott egyéneknél funkcionálisan is megemelkedett talpnyomásértékek jelennek meg a metatarsusoknál.…”
Section: Táblázatunclassified